Immigration and Democratic Principles: On Carens' Ethics of Immigration. Issue 4 (10th February 2016) - Song, Sarah
Abstract: Carens has done more than any other political theorist or philosopher to develop the normative perspective of prospective migrants from within the liberal democratic tradition, but he has not sufficiently engaged with the other side of the argument – in particular, with the value of political community and the principle of collective self‐determination. What is at stake for the immigrant‐receiving country that might justify its claim to control immigration? I first examine Carens' theory of social membership and its connection to political community. I then discuss his method of 'political theory from the ground up' and his interpretation of democratic principles. I conclude with a discussion of the principle of collective self‐determination.